Design and optimization of nano invasomal gel of Glibenclamide and Atenolol combination: in vitro and in vivo evaluation - P. Anitha; S. V. Satyanarayana (SpringerOpen, 2021)
Abstract Background There are many circumstances where chronic disease is associated with other disorders, especially in diseases such as diabetes with noncommunicable disease risk factors, such as hypertension. The current therapies for treating such chronic comorbid diseases are limited and challenging due to the difficulties in overcoming the side effects from complex therapeutic treatment regimen. The present study is aimed to develop and optimize the combinational nano invasomal gel of Glibenclamide (GLB) and Atenolol (ATN) as a novel combination therapy for comorbid treatment of diabetic hypertensive patients. The developed formulations were characterized for various parameters, including in-vitro skin permeation, skin irritation, in-vivo antidiabetic, and antihypertensive activities. Results OCNIG showed that the % entrapment efficiency of GLB is 96.67 ± 0.65% and % entrapment efficiency of ATN is 93.76 ± 0.89%, flux of GLB (240.43 ± 1.76 μg/cm2/h), and flux of ATN (475.2 ± 1.54 μg/cm2/h) which was found to conform to the expected value. The results indicated desired release and permeation profiles. Optimized formulation showed significant pharmacokinetic properties, which shows improvement in bioavailability by 134.30% and 180.32% respectively for two drugs, when compared to marketed oral preparation. Pharmacodynamic studies showed improved and prolonged management of diabetes and hypertension in Wistar rats, compared to oral and drug-loaded nano invasomes formulations. Conclusion Overall, the results showed that nano invasomal gel was found to be a useful and promising transdermal delivery system for the treatment of concurrent diseases.